PENGARUH KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM TERHADAP PRESTASI BELAJAR SISWA SDN 1 KAMARU - Rahim, Abd (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2022)
The purpose of this study was to determine the effect of the competence of Islamic Religious Education teachers on student achievement in SD Negeri 1 Kamaru. In this study, 22 students were used as samples. This research strategy utilizes quantitative data to reveal the truth about the form of the relationship between variables or phenomena. The number of test scores for the effect of PAI teacher competence on student achievement is 0.81, in accordance with the findings of this study that the impact index value obtained is positive. The competence of Islamic Religious Education teachers has a significant effect on student learning achievement. Teacher competencies are considered successful if they are able to actively involve students in the learning process physically, mentally, and socially, and increase students' self-confidence.